2021
DOI: 10.13057/biodiv/d220443
|View full text |Cite
|
Sign up to set email alerts
|

Coleoptera of the Penza region, Russia based on fermental crown trap

Abstract: Abstract. Ruchin AB, Egorov LV, Polumordvinov OA. 2021. Coleoptera of the Penza region, Russia based on fermental crown trap). Biodiversitas 22: 1946-1960. There are the results of processing the material of the 2019-2020 studies on Coleoptera from the Penza region, Russia. The surveys were carried out using fermental crown traps in various habitats on the territory of 18 districts of the region. In total, 18 traps were installed in 2019 and 96 traps – in 2020. During the research, 5,577 specimens were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
(55 reference statements)
2
6
1
Order By: Relevance
“…On the edges, glades, and meadows, this species is very common, and it is often seen on flowering plants. Previously, it was recorded very rarely in the fermental traps located in forest ecosystems [65,68,74]. In our studies, the maximum abundance and frequent occurrence were typical for glades and cuttings under power lines.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…On the edges, glades, and meadows, this species is very common, and it is often seen on flowering plants. Previously, it was recorded very rarely in the fermental traps located in forest ecosystems [65,68,74]. In our studies, the maximum abundance and frequent occurrence were typical for glades and cuttings under power lines.…”
Section: Discussionsupporting
confidence: 49%
“…Larvae feed on roots, but can also be carnivorous [83,84]. Earlier in the beer traps located in forest ecosystems, it was registered very rarely [65,68,74]. In our studies, it was not found only on a sandy spit.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Fauna lists are currently an important feature of faunal studies, given their important role in biological inventories at local and regional levels. These parameters contribute to the knowledge of the structure and composition of communities in a specific systematic group [1][2][3][4][5][6]. A recognized problem for biodiversity is the fragmentation of and reduction in ecosystems as a result of human activity [7][8][9].…”
Section: Discussionmentioning
confidence: 99%